The Effect of Probiotic Yoghurt on the Frequency of Salivary Candida - S Lesan; F Hajifattahi; M Rahbar; S Mohammadi (Islamic Azad University, 2017)
Background and aim: Oral candidiasis is the most common fungal disease, and it is often considered as a local opportunistic infection. Oral candidiasis is usually treated with local use of antifungal medications. Since probiotic bacteria have the ability to inhibit the growth of pathogens and modulate human immune responses, they could provide new possibilities in antifungal therapy. The aim of the present study was to examine the effect of probiotic yoghurt on the frequency of salivary candida. Materials and methods: This randomized double-blind crossover clinical trial involved 34 healthy adults divided to two groups: 17 subjects in case group (probiotic yoghurt) and 17 subjects in control group (regular yoghurt). At the beginning of the experiment and after 3 weeks of intervention (consumption of regular or probiotic yoghurt), saliva samples were collected from both groups and candida colonies were counted. After a two-week wash out period, the groups were interchanged (crossover study design), and the sampling process was repeated. The data were analyzed using Mann-U-Whitney and Chi-square tests. The level of significance was set at p<0/05. Results: Variations of salivary candida equaled 1.8±9.3 cfu/ml in regular yoghurt group and -3.8±7.9 cfu/ml in probiotic yoghurt group (p=0.01). The amount of salivary candida decreased in 47% of the cases in probiotic yoghurt group and in 29.4% of the cases in regular yoghurt group (p=0.07). Conclusion: The results of the present study showed that short-term consumption of probiotic yoghurt decreases the frequency of salivary candida colonies after 3 weeks.